THE ROLE OF MICROBIOTA IN CELLULAR HOMEOSTASIS AND MUTAGENESIS - VLADIMIR G. Druzhinin; VLADISLAV YU. Buslaev; ELIZAVETA D. Baranova; LYUBOV V. Nacheva (Фундаментальная и клиническая медицина)
The human body is currently considered as a meta-organism, evolutionarily inhabited by numerous microbes which populations evolve and adapt according to the changing conditions. The advent of high-throughput genomic and metabolomic approaches uncovered the complexity of interactions between the host and its microbiota, primarily mediated by synthesis of microbial bioactive compounds including mutagens. Alter-ations in microenvironment may disturb homeostasis of microbiota leading to the increased production of hazardous metabolites that, in turn, may initiate or promote disease development. Here we evaluate existing data on the role of human microbiota in physiological and pathological processes, with a particular focus on metabolomics.